Microbial Profiles of Retail Pacific Oysters (Crassostrea gigas) From Guangdong Province, China - Yu, Mingjia; Wang, Xiaobo; Yan, Aixian (Frontiers in Microbiology, 2021)
Oysters are one of the main aquatic products sold in coastal areas worldwide and are popular among consumers because of their delicious taste and nutritional value. However, the microorganisms present in oysters may pose health risks to consumers. In this study, the microbial communities of Pacific oysters (Crassostrea gigas) collected from aquatic product markets in three cities (Guangzhou, Zhuhai, and Jiangmen) of Guangdong Province, China, where raw oysters are popular, were investigated. The plate counts of viable bacteria in oysters collected in the three cities were all approximately 2 log colony-forming units/g. High-throughput sequencing analysis of the V3–V4 region of the 16S ribosomal DNA gene showed a high level of microbial diversity in oysters, as evidenced by both alpha and beta diversity analysis. Proteobacteria, Bacteroidetes, and Firmicutes were the dominant phyla of the microorganisms present in these samples. A variety of pathogenic bacteria, including the fatal foodborne pathogen Vibrio vulnificus, were found, and Vibrio was the dominant genus. Additionally, the relationship between other microbial species and pathogenic microorganisms may be mostly symbiotic in oysters. These data provide insights into the microbial communities of retail oysters in the Guangdong region and indicate a considerable risk related to the consumption of raw oysters.